2018
DOI: 10.1007/s10126-018-9822-8
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Probiotics Improves the Brine Shrimp Production and Prevents Detrimental Effects of Pathogenic Vibrio Species

Abstract: In this study, we evaluated a consortium of probiotic bacteria as an environmentally-friendly strategy for controlling pathogenic Vibrio species during the brine shrimp incubation period. Probiotic strains were initially selected on basis of (i) their ability to colonize the cyst surfaces, (ii) their absence of cross-inhibitory effects, and (iii) no detrimental effect on cyst hatching. The cysts and nauplius surfaces were immediately colonized after the application of selected probiotic strains, without detrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Most pathogens that impact aquaculture are deemed opportunistic, including Vibrio . Previous studies have reported that was closely related to the onset of various diseases and mass mortality of shrimp [ 10 , 11 , 13 ]. As expected, we observed significantly abundant Vibrio in gut microbiota of shrimps who did not survive as well (Additional file 1 : Table S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most pathogens that impact aquaculture are deemed opportunistic, including Vibrio . Previous studies have reported that was closely related to the onset of various diseases and mass mortality of shrimp [ 10 , 11 , 13 ]. As expected, we observed significantly abundant Vibrio in gut microbiota of shrimps who did not survive as well (Additional file 1 : Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…harvey that is a common cause of shrimp mortalities [ 10 ]. The probiotic consortium has demonstrated an effective way to reduce the abundance of pathogenic Vibrio species and to prevent the mortality during Vibrio challenges [ 13 ]. Such studies on shrimp have mainly focused on the physiological and immunological responses to the applied probiotics.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, the inoculation of 10 6 CFU ml -1 of Lactobacillus sp. in water reduced the prevalence of pathogenic Vibrio in brine shrimp culture (Quiroz-Guzmán et al, 2018). The Vibrionaceae reduction in shrimps fed the probiotic diet (Pro) resulted in an increase of Rhodobacteraceae family, which has been reported at higher abundance in healthy shrimp as compared to diseased shrimps (Dai et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Escobedo-Fregoso et al: Effect of dietary prebiotic inulin and probiotic Bacillus / XXIII (3): 50-57 (2021) Lactobacillus sp. and Bacillus subtilis as probiotics, has also proved to protect against pathogenic bacteria in shrimp (Balcázar and Rojas-Luna, 2007) and brine shrimp culture (Quiroz-Guzmán et al, 2018).…”
mentioning
confidence: 99%
“…In addition to the nutrients provided in the feed, farmers frequently top-dress their feed with vitamins, minerals, immune-stimulants, probiotics, and pond optimizers [ 20 , 21 ]. Top-dressing agents are perceived by the farmers to be feed attractants and growth promoters [ 22 , 23 ]. These agents have typically increased feed costs by US$39/ton in small-scale shrimp farming [ 24 ].…”
Section: Introductionmentioning
confidence: 99%